Genetics and clinical phenotype of Erdheim–Chester disease: A case report of constrictive pericarditis and a systematic review of the literature - Bartoli, Lorenzo; Angeli, Francesco; Stefanizzi, Andrea; Fabrizio, Michele; Paolisso, Pasquale; Bergamaschi, Luca; Broccoli, Alessandro; Zinzani, Pier Luigi; Galiè, Nazzareno; Rucci, Paola; Foà, Alberto; Pizzi, Carmine (Frontiers in Cardiovascular Medicine, 2022)
Background: Erdheim-Chester disease is a rare form of histiocytosis. An increasing number of genetic mutations has been associated with this syndrome, confirming its possible neoplastic origin. Recently, a connection between BRAF mutational status and a specific phenotype was described, however no studies have yet evaluated the correlations between other mutations and the clinical features of the disease. Objectives: To clarify the association between clinical phenotype and genetic mutations identified in the neoplastic cell lines of Erdheim-Chester disease (ECD). Methods: We describe a case of ECD, characterized by pericardial involvement and a KRAS mutation shared with chronic myelomonocytic leukemia. Hence, through a meta-analysis of individual participant data of all genetically and clinically described cases of Erdheim-Chester disease in the literature, we aimed to elucidate the association between its clinical phenotype and baseline genetic mutations. Results: Of 760 studies screened, our review included 133 articles published from 2012 to April 2021. We identified 311 ECD patients whose genotype and phenotype were described. We found 5 main genes (BRAF, KRAS, NRAS, PIK3CA, MAP2K1) whose mutation was reported at least three times. Mutation of BRAF led to a neurological disease (183 out 273 patients, 67%; p<0.001), KRAS and NRAS-mutated patients mainly showed a cutaneous (5 out of 6 patients, 83.3%, p<0,004) and pleural (4 out of 9 patient, 44%, p=0.002) involvement respectively, PIK3CA was not associated to a specific organ involvement, MAP2K1 mutations caused the disease to primarily involve the peritoneum and retroperitoneum (4 out 11, 36.4%, p=0.01). Conclusions: This work hints towards a possible influence of baseline mutation over the natural history of ECD, underscoring the importance of a thorough genetic analysis in all cases with the ultimate goal of identifying a possible targeted therapy for each patient.